2007
DOI: 10.1111/j.1460-9568.2007.05704.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐specific variability and a ‘cage effect’ independently mask a neuropathic pain quantitative trait locus detected in a whole genome scan

Abstract: Sex and environment may dramatically affect genetic studies, and thus should be carefully considered. Beginning with two inbred mouse strains with contrasting phenotype in the neuroma model of neuropathic pain (autotomy), we established a backcross population on which we conducted a genome-wide scan. The backcross population was partially maintained in small social groups and partially in isolation. The genome scan detected one previously reported quantitative trait locus (QTL) on chromosome 15 (pain1), but no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…A more sophisticated perspective is that sex and genetic background (and their interaction) are both simply components of inter-individual variability that need to be explained. As might be expected given this interaction, genes (quantitative trait loci) with sex-dependent effects on pain trait variability have been uncovered [38][39][40][41][42] . A recent study uncovered a three-way interaction in both mice and humans between sex, genetics (AVPR1A genotype (AVPR1A encodes the vasopressin 1A receptor)) and acute stress 43 .…”
Section: Male Onlymentioning
confidence: 91%
“…A more sophisticated perspective is that sex and genetic background (and their interaction) are both simply components of inter-individual variability that need to be explained. As might be expected given this interaction, genes (quantitative trait loci) with sex-dependent effects on pain trait variability have been uncovered [38][39][40][41][42] . A recent study uncovered a three-way interaction in both mice and humans between sex, genetics (AVPR1A genotype (AVPR1A encodes the vasopressin 1A receptor)) and acute stress 43 .…”
Section: Male Onlymentioning
confidence: 91%
“…65 Furthermore, nerve regeneration is more efficient in females due to hormonal influences 61,63,64 ; Kovavic et al reported a larger number of myelinated axons in the anastomosed nerve segment in females, which could be related to a higher sprouting capacity of thin myelinated sensory axons. 66 Nerve Despite the fact that neuromas and nerve injuries in general are far more common in the upper limb, most of the experimental models are designed on the hindlimb.…”
Section: Animal Model Animalmentioning
confidence: 98%
“…With this in mind, we ran a second experiment in which background autotomy levels were enhanced. Prior studies have shown that the tendency to autotomize is enhanced by social interactions in a group caging paradigm (Devor and Raber 1990;Devor et al 2007). Therefore, in a second, independent F 2 population (47 mice), phenotyping was done in cages containing one or two F 2 animals and one same-sex mouse of a high autotomy strain (C3H/Hen) that was nerve-injured and performed autotomy.…”
Section: Cacng2 Stargazer Micementioning
confidence: 99%